Effects of Heat as a Taphonomic Agent on Kerf Dimensions - Vegh, Emese Ilona; Rando, Carolyn (​Forensic Archaeology, Anthropology and Ecology, 2019)
The information that can be derived from the rate of preservation of cremated human remains is highly valuable for forensic anthropologists and bioarchaeologists. Especially when taphonomic agents, such as fire, are intentionally introduced to obscure lesions on the skeleton. When sharp force trauma is present on bones, one of the main questions that arise is whether it is possible to tell what instrument was used for trauma infliction. This study used quantitative methods to examine kerfs on bones treated with heat as a taphonomic agent. The experiment used three sharp-bladed weapons to inflict trauma on porcine long bones: a single bladed non-serrated kitchen knife, a hacksaw, and a wood saw. The traumatised bones along with control bones were burnt in controlled laboratory conditions at temperatures ranging from 300°C to 1000°C. Quantitative analysis was undertaken on scanning electron microscopy images. Shrinkage of the kerf dimensions were recorded only at 1000°C; excepting marks from the wood saw, which instead showed an increase in maximum width. Individualisation of the saws was not possible using only the metric traits. However, the class of the weapons (knife versus saw) could always be identified. It has been concluded that burning may cause fluctuation in kerf widths.